MOVING OF ABILMAMBET KHAN TO TURKESTAN AND CHANGES IN THE GOVERNMENT OF THE COUNTRY (1744-1769) - Майманова, Нуршат (Вестник ЗКУ, 2024)
Taking the reins of an independent republic and becoming a sovereign country gave us the opportunity to study our own history in a new way. In this regard, a lot of scientific research is being carried out in order to give a proper assessment to historical figures who have left a deep mark on the history of our country, from the point of view of national interests, and the white pages of our history being opened. This is due to the fact that in any civilized country historical science fulfills its humanistic task by studying the path of this country and people, especially in difficult historical periods, and the life path of individual historical figures who left a deep mark on history with their social activities during those periods. Moreover, recovering the historical truth about individuals whose historical destinies have been continuously distorted in every period is essential in restoring our national history today. After all, it is known that a national approach to historical figures forms a sense of patriotism in the younger generation.